Multidisciplinary Team Management of Hepatocellular Carcinoma in the MENA Region: Current Practices, Challenges, and Gaps - El-Kassas M; Khalifa R; AlNaamani KM; Shousha H; Yilmaz Y; Sanai FM; Almattooq M; Labidi A; Akroush MWI; Debzi N; Abdelmalek MO; Abdeen NS; et al. (Journal of Hepatocellular Carcinoma)
Mohamed El-Kassas,1,2 Rofida Khalifa,3 Khalid M AlNaamani,2,4 Hend Shousha,5 Yusuf Yilmaz,2,6 Faisal M Sanai,2,7 Maen Almattooq,2,8 Asma Labidi,2,9 Maisam WI Akroush,2,10 Nabil Debzi,2,11 Mohamed Omar Abdelmalek,12 Nermeen Sherif Abdeen,13 Ali Tumi,2,14 Mohamed Elbadry,1,2 Amr El Fouly,1 Eman Marwan,1 Jassim Al Suwaidi,15 Abdel-Naser Elzouki,2,16 Khalid A Alswat,2,17 On behalf of the Steatotic Liver Disease Study Foundation in Middle East and North Africa (SLMENA) CollaboratorsChikhi Yazid1. 1, Saidani Khadidja2. 2, Sherif Ahmed3. 3, Hanaa Fathelbab4. 4, Mohamed Kohla5. 5, Eman Barakat6. 6, Wessam Abdellatif7. 7, Mina Tharwat8. 8, Asmaa Mohammad9. 9, Sawsan Abd El-Moniem10. 10, Asem Elfert11. 11, Yasmeen Ahmed6. 6, Mohammed Ahmed12. 12, Usama Eldaly13. 13, Essam Hassan14. 14, Fawzi Abdel-Rahman15. 15, Munira Altarrah16. 16, Dalal Alhaqqan17. 17, Elhusain Kamoka18. 18, Mustapha Benazzouz19. 19, Rashid ALSukaiti20. 20, Itrat Mehdi21. 21, Asim Jamal Shaikh22. 22, Al Warith Al Hashmi23. 23, Kakil Rasul24. 24, Kanan Alshammari25. 25, Khalid Bzeizi26. 26, Adnan Alzanbagi27. 27, Haythem Yacoub28. 28, Amal Khsiba29. 29, Nour Elleuch30. 30, Ilker Turan31. 31, Murat Kiyici32. 32, Levent Doganay33. 33, Gökhan Kabaçam34. 34, Umit Karaogullarindan35. 35, Coskun Demirtas36. 36, Cem Simsek37. 37, Sezai Yilmaz38. 38, Murat Akyildiz39. 39, Dilara Turan Gökçe40. 40, Murat Dayangac41. 41, Murat Gülşen42. 42, Yasar Tuna43. 43, Sencan Acar44. 44, Derya Ari45. 45 On behalf of the Steatotic Liver Disease Study Foundation in Middle East and North Africa (SLMENA) Collaborators1.Interne Medicine Department, EPH Tipaza, Tipaza, Algeria.; 2.Faculty of Medicine, Algiers, Algeria.; 3.Hepatology and Gastroenterology Department, Faculty of Medicine, Zagazig University, Egypt.; 4.Tropical Medicine Department, Minia University, ElMinya, Egypt; 5.Hepatology and Gastroenterology Department, National Liver Institute, Shebeen El-Kom, Egypt.; 6.Tropical Medicine Department, Ain-Shams University, Cairo, Egypt.; 7.Radiology Department, National Hepatology & Tropical Medicine Research Institute, Cairo, Egypt.; 8.Tropical Medicine and Gastroenterology Department, Faculty of Medicine, Aswan University, Aswan, Egypt.; 9.Tropical Medicine and Gastroenterology Department, Sohag University, Egypt.; 10.Hepatology and Gastroenterology Unit, Mansoura, Egypt.; 11.Tropical Medicine Department, Tanta University, Egypt.; 12.Hepatology, Gastroenterology and Infectious Disease Department, Kafr Elsheikh, Egypt.; 13.Medical oncology Department, Damietta oncology Center, Egypt.; 14.Endemic Medicine Department, Fayoum University, Fayoum, Egypt.; 15.Private Sector, Amman, Jordan.; 16.Gastroenterology and Hepatology Department, Al Amiri Hospital, Kuwait City, Kuwait.; 17.Department of Gastroenterology, Mubarak AlKabeer Hospital, AlJabriya, Kuwait.; 18.Surgical Oncology Department, National Cancer Institute, Sabratha, Libya.; 19.Hepatology and Gastroenterology Department, Rabat International University, Rabat, Morrocco.; 20.Radiology and Nuclear Medicine, University Medical City, Muscat, Oman.; 21.Medical Oncology Department, The Royal Hospital, Muscat, Oman.; 22.Medical Oncology Department, Sultan Qaboos Comprehensive Cancer Care and Research Centre (SQCCCRC), Muscat, Oman.; 23.Hepatobiliary and liver Transplant Surgery, Royal Hospital, Muscat, Oman.; 24.Medical Oncology, NCCCR, Doha, Qatar.; 25.Department of Oncology, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia.; 26.Liver & Small Bowel Health Centre, King Faisal Specialist Hospital & Research Center Riyadh, Saudi Arabia.; 27.Gastroenterology Department, King Abdullah Medical City, Makkah, Saudi Arabia.; 28.Gastroenterology B Department, La Rabta Hospital, Tunis, Tunisie.; 29.Gastroenterology Department, Tunis El Manar University, Mohamed Tahar Maamouri Hospital Nabeul, Tunisia.; 30.Department of Gastroenterology, University of Sousse, Sousse, Tunisia.; 31.Gastroenterology Department, Ege University School of Medicine, Izmir, Turkey.; 32.Gastroenterology Department, Uludag University, Bursa, Turkey.; 33.Gastroenterology and Hepatology Department, Bau Medical School Pendik Medicalpar Hospital, İstanbul, Turkey.; 34.Liver Transplantation Department, Guven Hospital, Ankara, Turkey.; 35.Gastroenterology Department, Cukurova University, Adana, Turkey.; 36.Gastroenterology and Hepatology Department, Marmara University School of Medicine, Istanbul, Türkiye.; 37.Gastroenterology Department, Hacettepe, Ankara, Turkey.; 38.Liver Transplantation Institute, Inonu University, Malatya, Türkiye.; 39.Gastroenterology and Liver Transplantation, Koc University Hospital, Istanbul, Turkey.; 40.Gastroenterology Bilkent City Hospital, Ankara, Türkiye; 41.Department of Hepatobiliary Surgery and Liver Transplantation Istanbul Medipol University, Istanbul, Türkiye; 42.Gastroenterology Department, Gaziantep University, Gaziantep, Türkiye; 43.Antalya Medicalpark Gastroenteroloji, Medicalpark Antalya, Antalya, Turkey; 44.Gastroenterology Department, Istanbul Florence Nightingale Hospital, Istanbul, Türkiye; 45.Gastroenterology Department, Ankara Bilkent City Hospital, Ankara, Turkey; 1Endemic Medicine Department, Faculty of Medicine, Helwan University, Cairo, Egypt; 2Steatotic Liver Diseases Study Foundation in Middle East and North Africa (SLMENA), Cairo, Egypt; 3Tropical Medicine Department, Faculty of Medicine, Minia University, Minya, Egypt; 4Department of Medicine, Division of Gastroenterology and Hepatology, The Medical City for Military and Security Services, Muscat, Oman; 5Endemic Medicine and Hepato-Gastroenterology Department, Cairo University, Cairo, Egypt; 6Department of Gastroenterology, School of Medicine, Recep Tayyip Erdoğan University, Rize, Turkey; 7Gastroenterology Section, Department of Medicine, King Abdulaziz Medical City, King Abdullah International Medical Research Center, Ministry of National Guard - Health Affairs, Jeddah, Saudi Arabia; 8Gastroenterology and Hepatology Department, Jaber AlAhmad Hospital, Kuwait City, Kuwait; 9Department of Gastroenterology “A”, Rabta Hospital, Tunis, Tunisia; 10Digestive and Liver Disease Clinic, Private Sector, Faculty of Medicine, Jordan University, Amman, Jordan; 11Hepatology Department, Mustapha Bacha University Hospital, Algiers, Algeria; 12Tropical Medicine and Gastroenterology Department, Assiut University, Assiut, Egypt; 13Tropical Medicine Department, Faculty of Medicine, Alexandria University, Alexandria, Egypt; 14Medical Department, Central Hospital, Tripoli, Libya; 15Scientific, Academic, and Faculty Affairs, Hamad Medical Corporation, Doha, Qatar; 16Department of Medicine, Hamad Medical Corporation and College of Medicine, Qatar University, Doha, Qatar; 17Liver Disease Research Center, Department of Medicine, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Mohamed El-Kassas, Endemic Medicine Department, Faculty of Medicine, Helwan University, Ain Helwan, 11795, Cairo, Egypt, Tel + 20 111 445 5552, Email m_elkassas@hq.helwan.edu.egPurpose: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality, with a high disease burden in the Middle East and North Africa (MENA) region. Multidisciplinary teams (MDTs) are essential for optimizing HCC management; however, their implementation and impact may vary across healthcare settings. This study evaluates the structure, decision-making processes, and challenges faced by MDTs in HCC treatment centers across the MENA region.Patients and Methods: This cross-sectional, multicenter study surveyed representatives from 53 HCC treatment centers across 38 cities in 11 MENA countries. A structured questionnaire was electronically distributed to assess MDT composition, meeting frequency, decision-making processes, adherence to clinical guidelines, patient management pathways, and challenges in HCC treatment.Results: Among the surveyed centers, 84.9% (n=45) reported having an established MDT. The most common specialties involved in MDT composition were hepatology (100%), interventional radiology (97.8%), medical oncology (91.1%), and hepatobiliary surgery (80%). Barcelona Clinic Liver Cancer staging was used in 95.6% of centers. Despite acknowledging MDT benefits, major challenges were documented by participants, including resource limitations (13.2%), financial constraints (13.2%), patient nonadherence (9.4%), and limited access to advanced technology (11.3%). Telemedicine was underutilized (9.4% of centers), and only 15.1% experienced participation in clinical trials.Conclusion: Our result highlights the pivotal role of MDTs in HCC management in the MENA region, demonstrating adherence to evidence-based guidelines and exposing critical gaps in resource availability, technology integration, and patient-centered decision-making. Strengthening MDTs through enhanced resource allocation, digital health adoption, and increased clinical trial participation is essential to improving HCC outcomes in the region.Plain Language Summary: This study identifies critical gaps in multidisciplinary hepatocellular carcinoma (HCC) management across the Middle East and North Africa (MENA). Despite recognizing multidisciplinary teams’ value, inconsistent implementation, fragmented referral pathways, limited diagnostic tool accessibility, and insufficient public awareness significantly hinder optimal patient care. Addressing these gaps urgently requires integrated national policies, expanded diagnostic infrastructure, enhanced clinician training, structured referral systems, and stronger public and patient engagement strategies. The study underscores the necessity for a strategic, coordinated approach to improve clinical outcomes and reduce the healthcare burden of HCC in the region.Keywords: hepatocellular carcinoma, multidisciplinary team, MENA region, cancer management, clinical decision-making